2018
DOI: 10.1371/journal.pone.0201189
|View full text |Cite|
|
Sign up to set email alerts
|

Anxiety and the severity of Tension-Type Headache mediate the relation between headache presenteeism and workers’ productivity

Abstract: The primary objective of this study was to explore the mechanisms and conditions whereby Tension-Type Headache (TTH) presenteeism relates to health-related loss of productivity as a result of both reduced physical and mental health. To this end, Structural Equation Modeling (SEM) was used to conduct a secondary data analysis of a randomized clinical trial involving 78 Tension-type Headache (TTH) patients. The results showed that TTH presenteeism did not directly relate to health-related loss of productivity, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…The HA+ patients revealed slightly higher, but non-significant levels of disability and unemployability. Monzani et al determined a correlation between headache intensity and loss of workers' productivity in patients suffering from tension-type headache [45]. A recent comprehensive meta-ethnographic systematic analysis describes chronic headache as "driver of behavior' which subsequently provokes a feeling of "a loss of control" in patient's life.…”
Section: Discussionmentioning
confidence: 99%
“…The HA+ patients revealed slightly higher, but non-significant levels of disability and unemployability. Monzani et al determined a correlation between headache intensity and loss of workers' productivity in patients suffering from tension-type headache [45]. A recent comprehensive meta-ethnographic systematic analysis describes chronic headache as "driver of behavior' which subsequently provokes a feeling of "a loss of control" in patient's life.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to workaholism (Balducci et al, 2020;Gorgievski et al, 2010), presenteeism which is considered to be more transitory and situational (George et al, 2017) has been found to be constantly associated with lower levels of work performance (Gillet et al, 2020b;Miraglia & Johns, 2016), especially in the nursing profession (Li et al, 2019;Rainbow, 2019). This may be explained by higher anxiety (Monzani et al, 2018) or lower psychological health (Li et al, 2019). Moreover, the ill-being that accompanies presenteeism should drain energy and divert attention so that performance ratings declines (Miraglia & Johns, 2016).…”
Section: Background the Negative Outcomes Of Workaholism And Presenteeismmentioning
confidence: 99%
“…A comprehensive and up-todate review of empirical research including studies from Korea using new modalities will be very helpful and can be the basis for recommendations regarding psychological treatment for primary headaches as a stand-alone treatment option or additional treatment with other treatment modalities in Korea. 4,11…”
Section: Discussionmentioning
confidence: 99%